Política de recursos humanos del personal civil de la administraçión pública directa: um estudio comparado entre Brasil y Colombia a nível federal e nacional respectivamente - Garcia Sampayo, Adayanith (1997)
The present work has the aim of studying, in a comparative way , the policies of development and valuing of human resources that have been defmed since the 1930s', in the governrnents of Brazil and Colombia, determining actions that have been adopted, at present, in the public to which they apply, civil public functionaries at federal and national leveIs, respectively, of direct administration. To address the aforementioned discussion, we have made a description of the experiences of reformation that these countries have gone through, aiming at the modernization of public administration. In our analysis, we made use of a qualitative methodology of identification and questioning of information.